Habitat characteristics, population structure, distribution, and regeneration status of Taxus wallichiana in South Vietnam - NGUYEN VAN HOP; CHEN CHANG XIONG; NGUYEN VAN QUY; NGUYEN THI LUONG (Nusantara Bioscience, 2023)
Abstract. Hop NV, Xiong CC, Quy NV, Luong NT. 2023. Habitat characteristics, population structure, distribution, and regeneration status of Taxus wallichiana in South Vietnam. Nusantara Bioscience 15: 179-188. Taxus wallichiana Zucc. is an endangered plant species with high economic value, making it threatened to extinction. Biological information about this species is therefore essential for its conservation. This study is aimed to assess the habitat characteristics, population structure, distribution, and regeneration status of T. wallichiana in South Vietnam. Vegetation surveys were conducted from 2016 to 2021 in three regions in Lam Dong Province. The study revealed that it was distributed in regions with monsoon climate with a total extent of ??379.57 ha, with habitats located on the hillside, narrow shelves, dissected terrain, high slope, on feralite soil with light brown to yellow, red, the soil layer thickness over 0.3 m and in clusters or streaks. The study recorded 634 trees with a diameter at breast height (DBH)?25 cm and 137 trees with 6 cm ?DBH<25 cm. The trees were found primarily at 1401-1500 m above sea level in a mixed broadleaved-coniferous forest. The growth indicators of DBH and overall height (Hvn) developed strongly, but the stand volume was low owing to low tree density. The exponential function was the most suitable for simulating the relationship between Hvn and DBH. Seven thousand six hundred and seventy-three regenerating young individuals were recorded with low density. The density of the regenerating trees decreased as the tree height increased. The finding of this study suggests that T. wallichiana faces the danger of extinction, so solutions are required to conserve and develop this threatened species.